2020
DOI: 10.1063/5.0005792
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian chaos in steady three-dimensional lid-driven cavity flow

Abstract: Steady three-dimensional flows in lid-driven cavities are investigated numerically using a high-order spectral-element solver for the incompressible Navier–Stokes equations. The focus is placed on critical points in the flow field, critical limit cycles, their heteroclinic connections, and on the existence, shape, and dependence on the Reynolds number of Kolmogorov–Arnold–Moser (KAM) tori. In finite-length cuboidal cavities at small Reynolds numbers, a thin layer of chaotic streamlines covers all walls. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 96 publications
1
13
0
Order By: Relevance
“…This resembles a localised three-dimensional version of a two-dimensional Moffatt eddy (Moffatt 1964) and is, in fact, a three-dimensional saddle focus, similar to what is found in a three-dimensional lid-driven cavity flow (see e.g. figure 6 c in Romanò, Türkbay & Kuhlmann (2020 b )). Obviously, the small counter-rotating vortex in figure 4( d ) does not arise in the case of a sphere in its fixed point when the wall moves towards the edge (figure 4 a – c ), because the velocity a fixed sphere rotating with the same angular velocity induces at the periphery of the corner eddy is much smaller than the velocity induced by the moving wall at the same location.…”
Section: Resultssupporting
confidence: 67%
“…This resembles a localised three-dimensional version of a two-dimensional Moffatt eddy (Moffatt 1964) and is, in fact, a three-dimensional saddle focus, similar to what is found in a three-dimensional lid-driven cavity flow (see e.g. figure 6 c in Romanò, Türkbay & Kuhlmann (2020 b )). Obviously, the small counter-rotating vortex in figure 4( d ) does not arise in the case of a sphere in its fixed point when the wall moves towards the edge (figure 4 a – c ), because the velocity a fixed sphere rotating with the same angular velocity induces at the periphery of the corner eddy is much smaller than the velocity induced by the moving wall at the same location.…”
Section: Resultssupporting
confidence: 67%
“…However, the size, location, and structure of the KAM tori are different due to the curvature of the moving walls. For the present system with curved moving walls we have reconstructed the KAM tori at Re = 400 in the same Romanò, Türkbay & Kuhlmann (2020). Owing to the point symmetry of the flow in a single cell, all KAM tori arise as two point-symmetric sets of tori.…”
Section: Numerical Flow Topologymentioning
confidence: 99%
“…For the present system with curved moving walls we have reconstructed the KAM tori at in the same way as in Romanò et al. (2017), Romanò, Hajisharifi & Kuhlmann (2017) and Romanò, Türkbay & Kuhlmann (2020). Owing to the point symmetry of the flow in a single cell, all KAM tori arise as two point-symmetric sets of tori.…”
Section: Transport Of Particlesmentioning
confidence: 99%
“…The Froude number and capillary number extinct at the limits of increasing Reynold's numbers. The chaotic mixing in lid-driven cavities has been analysed by [18,19]. They found that in general terms, at lower Reynolds number the chaotic mixing can be more important than higher Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%